(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the main components of a healthy lifestyle in students from the perspective of modern hygiene: rational nutrition, sufficient sleep duration and quality, as well as regular physical activity. Based on documents of the World Health Organization, the CDC, and publications from recent years, it is shown that stable behavioral habits have a direct impact on overall health status, psycho-emotional well-being, work capacity, and academic performance. A healthy student regimen cannot be reduced to a single isolated factor. The effect is achieved through a combination of balanced and safe nutrition, adherence to a sleep schedule, limitation of evening stimulation, reduction of sedentary time, and fulfillment of the minimum recommended levels of physical activity. The need for comprehensive preventive programs in higher education institutions, including educational activities, the creation of a healthy environment, and institutional support for beneficial habits, is substantiated.